The impact of myofascial release and stretching techniques on the clinical outcomes of migraine headache: A randomized controlled trial - Tahere Rezaeian (Journal of Research in Medical Sciences, 2021)
Background: Migraine patients often have painful trigger points, especially in the area of head and neck. Thus, we aimed to investigate the effect of myofascial release and stretching techniques in the management of migraine headache. Materials and Methods: This was a randomized controlled trial study on 40 migraine patients. The subjects in the experimental group received three sessions with a duration of 20 min per session techniques. Databases were analyzed using 2 × 3 repeated-measures analyses of variance (P < 0.05). Results: Experimental group showed a significant reduction in pain intensity (P < 0.001) and the neck disability index score (P < 0.001) and an increase in cervical range of motion (P < 0.001) in all time points after the intervention as compared with baseline and control group (P < 0.001). Conclusion: Myofascial release and stretching techniques were effective in improving symptoms in patients with migraine headache.